The Impact of Cattle Grazing on Recreational Ecosystem Services in a Park Area: a Gray Water Footprint Assessment - Allocca, V.; Marzano, E.; Tramontano, M.; Celico, F. (Journal of Environmental Accounting and Management, 2026)
In park areas (PAs), restrictions on anthropogenic activities are often established to achieve the long-term conservation of nature and its associated ecosystem services and cultural values. The economic literature on freshwater ecosystem services has identified the depletion of aquatic ecosystem quality as a crucial issue, suggesting appropriate methods to evaluate this degradation in monetary terms. An alternative approach is water footprint accounting, which is employed in this study to evaluate scarcity and quality issues originating from groundwater depletion in a dynamic setting. In this study, we evaluate the impact of cattle grazing on groundwater-related ecosystem services in a karst environment located within the Monti Picentini Regional Park, located in the Campania region in southern Italy. In so doing, we guide policy makers to achieve sustainable environmental and socioeconomic management decisions for the target ecosystem to balance the competitive uses of freshwater ecosystem services in the Monti Picentini Park Area.